อิทธิพลของการผสมพอลิโพรไพลีนที่นำกลับมาหลอมใหม่ต่อคุณสมบัติเชิงกลและดัชนีการหลอมไหล - จิระเชษฐ์ บุญแก้ว (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
To study on effect of blending ratio and forming temperature of virgin polypropylene (PP) blended with recycled polypropylene (PR) on physical and mechanical properties. Forming temperatures of the polymer blends which between 170 to 270°C were studied. The blending ratios of the polymers were that of 33, 100, 300 and 900 parts per hundred PP resin (phr). The dry blends were molten using hot press at 50 kg/cm2 for 15 minutes. There were two steps of the experiments that (1) studying the effect of forming temperatures and blending ratio of the 1st time recycled polypropylene, and (2) studying the effect of blending ratios and numbers of re–process polypropylene from 1 to 6 times. The physical and mechanical properties of the specimens obtained were performed such as melt flow index, microstructure, specific gravity, tensile strength, modulus of elasticity, hardness and impact strength. The experimental results were found that (1) the PP reproduced with less than 3 times could be blended with the virgin PP up to 900 phr having still the stability, (2) melt flow index increased with increasing of temperature and the numbers of re–process, (3) the specific gravity, hardness and impact strength of the polymers blended with the first time recycled, which were not changed with the compositions being less than 900 phr and the temperature during 190–240°C with the statistical confidential interval of 95%, had the averages of 0.901±0.002, 73.6±0.1 (shore D), and 4.47±0.03 kJ/m2 respectively, whereas the tensile strength and modulus of elasticity were 34.2±0.1 MPa, and 753±0.2 MPa respectively. However, the tensile strength and modulus of elasticity were decreased when the temperatures were higher than 245°C, and (4) the increasing of the compositions and number of reprocesses of the polymer led the small patchworks and more semicrystallized which provided the impact strength and elongation at break decreased while the tensile strength, modulus, and hardness of elastic and hardness increased.